A clustering WSN routing protocol based on k-d tree algorithm - Anzola, John; Pascual, Jordán; Tarazona, Giovanny; González-Crespo, Rubén (Sensors, 2019)
Clustering in wireless sensor networks has been widely discussed in the literature as a strategy to reduce power consumption. However, aspects such as cluster formation and cluster head (CH) node assignment strategies have a significant impact on quality of service, as energy savings imply restrictions in application usage and data traffic within the network. Regarding the first aspect, this article proposes a hierarchical routing protocol based on the k-d tree algorithm, taking a partition data structure of the space to organize nodes into clusters. For the second aspect, we propose a reactive mechanism for the formation of CH nodes, with the purpose of improving delay, jitter, and throughput, in contrast with the low-energy adaptive clustering hierarchy/hierarchy-centralized protocol and validating the results through simulation.
Keywords: k-d tree algorithm; hierarchical protocol; quality of service; routing protocol; WSN; clustering; JCR; Scopus